2019
DOI: 10.3126/nepjoph.v11i1.25422
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Melanoma: Our Experience

Abstract: Background: Choroidal melanomas are diagnosed in approximately 6 out of one million Americans per year, and although their incidence is low, they are the most common primary intraocular tumor in adults. Methods: Choroidal melanoma is rare tumors and till date no such reports with sclera involvement has been reported from Nepal. It is a prospective case series. The aim of this study is for awareness of the severity of the Choroidal melanoma and it’s management. Besides, it is also to study the demography,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…The mean age of presentation is around 42.9-63.5 years in Asians according to different studies [4][5][6][7][8][9][10][11][12][13][14][15][16]. Only 2 studies conducted in Japan and Israel have shown mean presenting age above 60 years [7,8].…”
Section: Agementioning
confidence: 99%
“…The mean age of presentation is around 42.9-63.5 years in Asians according to different studies [4][5][6][7][8][9][10][11][12][13][14][15][16]. Only 2 studies conducted in Japan and Israel have shown mean presenting age above 60 years [7,8].…”
Section: Agementioning
confidence: 99%
“…Despite successful eradication of the tumour, up to 50% of choroidal melanoma patients develop metastatic disease (typically to the liver) [2]. Due to its latency and metastatic potential, the mortality of choroidal melanoma is approximately 50% [3]. Once choroidal melanoma metastasizes, the median survival time after detection of the first metastasis is 8 months [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the epithelioid confers the worst prognosis and is more commonly observed in metastases. The mixed melanoma subtype is thought to represent a transitional phenotypic entity [2][3]. Predictors of tumor behavior associated with poor prognosis are well established; size >15 mm in the maximal linear dimension of tumor growth, necrosis, depth of invasion, scleral and ciliary body involvement, anterior and juxtapapillary locations, extrascleral tumor extension, cytologic and cytogenetic features (gain of chromosome 8 and loss of chromosome 3) [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%